BASIC CONVERSATION SEBAGAI EMBRIOKAMPUNG INGGRIS DI KELURAHAN KRATON KECAMATAN MAOSPATI TAHAP I (Eduscotech, 2022)
This community service project aims to analyze the implementation of the Basic Conversation program as the initial phase in developing an English Village in Kraton Village, Maospati District. The program is designed to enhance the English-speaking abilities of local residents through a practical, structured, and community-oriented approach as the foundation for establishing a sustainable English Village. This study employs community action research with a qualitative approach, involving the active participation of residents, educators, and community leaders. The Basic Conversation program was delivered through intensive training that incorporated daily conversation practice, role-plays, and group discussions facilitated by competent instructors. The results indicate that the program significantly improved participants’ basic speaking skills, boosted their self-confidence, and strengthened social interaction within the community. Furthermore, the program increased community awareness of the importance of English proficiency in supporting social and economic mobility. Based on these findings, it is recommended that the program be expanded and continued with a more advanced curriculum and stronger collaboration with stakeholders, including local government and the private sector, to achieve a self-sustaining English Village model.